THE PATIENT SAFETY CULTURE IN REDUCING ADVERSE EVENTS: EFFECTIVE PATIENT SAFETY GOALS OF QUALITATIVE STUDY IN HOSPITAL X MEDAN: PATIENT SAFETY CULTURE - Adristi, Yasmin; Lubis, Irwansyah; Arifah, Cahyani; Hasibuan, Elvida Wati; Wiyanto, Bunga; Sirait, Nabila Azkiyah; Shafira, Ananda Dwi; Afifah, Siti Fadillah; Alvionita, Elsti (STIKes Mandala Waluya Kendari, 2025)
Background: Patient safety is a key factor in healthcare services, but in reality, there are still many cases of patients being injured while receiving care in healthcare settings, with impacts ranging from minor injuries to death. This study aims to evaluate the implementation of patient safety culture at Hospital X, especially the understanding, practices, and challenges faced by health workers. Methods: The qualitative phenomenological method was used with purposive sampling, involving 7 informants (1 head of staff and 6 nurses) from the ward and TB Polyclinic. Data were collected through in-depth interviews, observations, and document studies, then analyzed using the Collaizi technique. Results: The study showed that all informants understood the importance of patient safety culture as a basis for quality services. The six patient safety targets have been implemented well, supported by team communication and clear responsibilities. The main obstacles are the lack of nursing staff and facilities such as bed dividers. Management support and team collaboration were assessed positively, while informants' expectations include ongoing training, increased resources, and routine evaluations. Conclusion: The study states that the implementation of patient safety culture at Hospital X Medan has been carried out with adequate awareness, although improvements are needed in consistency and availability of resources. Collaboration between management and health workers is needed to strengthen this culture sustainably.